Social media video analysis methodology for sarin exposure - Sadik Toprak; Emine Yilmaz Can; Bulent Altinsoy; John Hart; Zekeriya Dogan; Mustafa Ozcetin (Oxford University Press, 2020)
As social media becomes increasingly ubiquitous, many events are recorded and released on social media platforms, including chemical weapon attacks. We develop an objective tool in order to evaluate brief and unstructured social media videos for analysing sarin exposure from a civilian medical pathology perspective. We developed and validated this new questionnaire using a standardized procedure that includes content domain specification, item pool generation, content validity evaluation, a pilot study, and assessment of reliability and validity. In total, 51 sarin attacks and 48 matched videos were analysed. Cronbach's α for all 20 items was 0.75, which indicates adequate internal reliability. The test-retest reliability was 0.96, which indicates good internal reliability. The inter-observer intraclass correlation coefficient was 0.97. After verifying sampling adequacy with the Kaiser-Meyer-Olkin measure and the factorability of the items with Barlett's test of sphericity, a factor analysis was performed. According to the principal axis factoring, a six-factor solution explained 51.86% of the total variance. The receiver-operating characteristic curve analysis showed that the Video Score Questionnaire has a sensitivity of 0.817, a specificity of 0.478, and an efficiency of 65.3. Therefore, the Video Score Questionnaire is reliable and valid for evaluating sarin attacks from brief and unstructured social media videos. Key points Chemical weapons are still used as a method of warfare. Social media videos are an important source of information. We developed a validated scale which can analyse sarin exposure in short and unstructured videos.